THE EFFECT OF CAFFEINE SUPPLEMENTATION ON PHYSICAL PERFORMANCE, RECOVERY AND SLEEP QUALITY IN ATHLETES – A LITERATURE REVIEW FROM THE LAST 5 YEARS - Weronika Lusarczyk; Natalia Sapeda; Aleksandra Białas; Aleksandra Młocek; Adrianna Truszyńska-Zawisza; Zuzanna Romanowska; Karolina Gorczyca (International Journal of Innovative Technologies in Social Science, 2025)
This review summarizes current evidence on the multifaceted effects of caffeine supplementation in the context of physical performance and recovery. Caffeine has been shown to enhance endurance, strength, power, and cognitive functions essential for competitive sports through physiological and neurological mechanisms. Additionally, caffeine contributes to recovery by reducing muscle soreness, accelerating neuromuscular restoration, and supporting mental readiness. However, its impact on sleep quality and duration presents a significant challenge, as improper timing or excessive intake can impair recovery and performance. Individual variability in caffeine metabolism and sensitivity necessitates personalized strategies to maximize benefits while minimizing adverse effects such as gastrointestinal discomfort, cardiovascular stimulation, nervousness, and dependence. Careful consideration of dosage, timing, and individual health status is crucial for safe and effective caffeine use in athletic populations. Overall, caffeine remains a valuable ergogenic aid when integrated thoughtfully into training and recovery regimens.